2005
DOI: 10.1371/journal.pbio.0030331
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Mesenchymal–Epithelial Interactions in the Hair Follicle

Abstract: De novo hair follicle formation in embryonic skin and new hair growth in adult skin are initiated when specialized mesenchymal dermal papilla (DP) cells send cues to multipotent epithelial stem cells. Subsequently, DP cells are enveloped by epithelial stem cell progeny and other cell types to form a niche orchestrating hair growth. Understanding the general biological principles that govern the mesenchymal–epithelial interactions within the DP niche, however, has been hampered so far by the lack of systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
475
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(518 citation statements)
references
References 53 publications
(73 reference statements)
32
475
2
2
Order By: Relevance
“…During in vitro culture, hDSPCs, which exhibited stem celllike characteristics in our previous study, gradually lose the expression of transcription factors associated with multipotency and self-renewal, such as SOX2 and NANOG for maintaining the characteristics of stem cells. Several previous reports suggested that the quality of the stem cells strongly depend on the culture method (Driskell et al, 2012;Grayson et al, 2007;Kuroda et al, 2010;Minchenko et al, 1994;Reiter et al, 2008;Ren et al, 2006;Rendl et al, 2005). Thus, we investigated whether hDSPCs retain their stemness in various culture conditions despite long-term culture.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…During in vitro culture, hDSPCs, which exhibited stem celllike characteristics in our previous study, gradually lose the expression of transcription factors associated with multipotency and self-renewal, such as SOX2 and NANOG for maintaining the characteristics of stem cells. Several previous reports suggested that the quality of the stem cells strongly depend on the culture method (Driskell et al, 2012;Grayson et al, 2007;Kuroda et al, 2010;Minchenko et al, 1994;Reiter et al, 2008;Ren et al, 2006;Rendl et al, 2005). Thus, we investigated whether hDSPCs retain their stemness in various culture conditions despite long-term culture.…”
Section: Discussionmentioning
confidence: 92%
“…It is also difficult to obtain adult stem cells because of their limited quantities in the tissue. According to some previous literatures, they are considered to be composed of 0.01% to 0.001% of the total cell number (Hill et al, 2012;Rendl et al, 2005;Riekstina et al, 2009;Shim et al, 2013;Wegner and Stolt, 2005;Wu et al, 2010). We found that hDSPCs in small quantity gradually lose pluripotency and the ability to proliferate once they are grown over long-term culture.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Loss of Nfatc1 stimulates bulge SC proliferation and anagen progression through loss of CDK4 repression (Horsley et al 2008). Transcriptional profiling showed that DP cells express a number of BMP receptors and several BMPs, the most potent being BMP6, promoting the maintenance of the DP-inductive properties upon in vitro culture (Rendl et al 2005(Rendl et al , 2008. Accordingly, conditional ablation of BMPR1a specifically in DP cells in vivo results in loss of the DP-inductive capacity in HF reconstitution assays (Rendl et al 2008).…”
Section: Hf Morphogenesis and Cyclingmentioning
confidence: 99%